REST levels affect the functional expression of voltage dependent calcium channels and the migratory activity in immortalized GnRH neurons. (26th August 2016) - Antoniotti, Susanna; Ruffinatti, Federico Alessandro; Torriano, Simona; Luganini, Anna; D'Alessandro, Rosalba; Lovisolo, Davide
Graphical abstract: Highlights: We downregulated REST transcription factor in neuronal GN11 cell line by silencing. 994-D4 clone, expressing low REST levels, showed a reduced migratory potential. REST silencing increased expression of functional voltage-dependent Ca 2+ channels. Enhancement of depolarization-induced calcium signals is dependent on P/Q channels. Abstract: The repressor element-1 silencing transcription factor (REST) has emerged as a key controller of neuronal differentiation and has been shown to play a critical role in the expression of the neuronal phenotype; however, much has still to be learned about its role at specific developmental stages and about the functional targets affected. Among these targets, calcium signaling mechanisms are critically dependent on the developmental stage and their full expression is a hallmark of the mature, functional neuron. We have analyzed the role played by REST in GN11 cells, an immortalized cell line derived from gonadotropin hormone releasing hormone (GnRH) neurons at an early developmental stage, electrically non-excitable and with a strong migratory activity. We show for the first time that functional voltage-dependent calcium channels are expressed in wild type GN11 cells; down-regulation of REST by a silencing approach shifts these cells towards a more differentiated phenotype, increasing the functional expression of P/Q-type channels and reducing their migratory potential.